2023
DOI: 10.3389/fphar.2023.1188926
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the therapeutic potentials of statins in cancer

Abstract: The widespread clinical use of statins has contributed to significant reductions of cardiovascular morbidity and mortality. Increasing preclinical and epidemiological evidences have revealed that dyslipidemia is an important risk factor for carcinogenesis, invasion and metastasis, and that statins as powerful inhibitor of HMG-CoA reductase can exert prevention and intervention effects on cancers, and promote sensitivity to anti-cancer drugs. The anti-cancer mechanisms of statins include not only inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 144 publications
0
4
0
Order By: Relevance
“…As famous and developed inhibitors of HMGCR, statins mediate the reduction of cholesterol and lead to interruption of their cell membrane structure and related biological functions, such as angiogenesis, apoptosis, and autophagy. Accumulating preclinical and clinical trials of statins in different cancers suggested an overall beneficial role of statins with a favorable safety profile in cancer treatment and prevention [149]. In some established meta-analysis studies, statin use was correlated with reduced risk of cancer development and cancer-specific mortality in cancer patients and was associated with favorable survival outcomes [150][151][152].…”
Section: Inhibitors and Clinical Therapeutic Implicationsmentioning
confidence: 99%
“…As famous and developed inhibitors of HMGCR, statins mediate the reduction of cholesterol and lead to interruption of their cell membrane structure and related biological functions, such as angiogenesis, apoptosis, and autophagy. Accumulating preclinical and clinical trials of statins in different cancers suggested an overall beneficial role of statins with a favorable safety profile in cancer treatment and prevention [149]. In some established meta-analysis studies, statin use was correlated with reduced risk of cancer development and cancer-specific mortality in cancer patients and was associated with favorable survival outcomes [150][151][152].…”
Section: Inhibitors and Clinical Therapeutic Implicationsmentioning
confidence: 99%
“…Mevalonate pathway products, such as isopentenyl pyrophosphate (IPP), farnesyl pyrophosphate (FPP), and geranylgeranyl pyrophosphate (GPP), all enable protein prenylation of GTPases, mainly Ras and RhoA proteins [59]. Limitations on these processes impede the alteration of various cancer pathways, thereby increasing apoptosis while decreasing angiogenesis, inflammation, and metastasis [60]. All of which are crucial in the fight against cancer development and progression.…”
Section: Basic Understanding Of the Molecular Mechanism Of The Anti-c...mentioning
confidence: 99%
“…It demonstrates that statins are anti-angiogenic. This anti-angiogenic outcome of statins in cholesterol-independent patients is accomplished by inhibiting the RhoA/focal adhesion kinase/AKT pathways [60]. The initial development of tumor blood vessels, relying on endothelial progenitor cells through vasculogenesis, could be disrupted by statins, potentially impeding tumor growth.…”
Section: Basic Understanding Of the Molecular Mechanism Of The Anti-c...mentioning
confidence: 99%
“…Clinical applications of ATOR in SCLC patients with dyslipidemia have been reported [14]. Recently, increasing preclinical and epidemiological evidence has been provoked that dyslipidemia is an important risk factor for carcinogenesis, statins are shown to exert possible prevention and intervention effects on cancers and promote sensitivity to anticancer drugs [15]. This study addressed the molecular and biochemical mechanisms of the antitumor e cacy of the co-treatment with ATOR and bevacizumab in the lung cancer mice model.…”
Section: Introductionmentioning
confidence: 96%